THE EFFECT OF USING QUIZIZZ LEARNING MEDIA ON STUDENTS’ LEARNING OUTCOMES IN PANCASILA EDUCATION FOR GRADE XI STUDENTS OF SMAN 1 KAMANG MAGEK, AGAM REGENCY, WEST SUMATRA - Aulia, Rahma; Supentri; Arianto, Jumili (Yayasan Amanah Nur Aman, 2025)
This research was motivated by students’ learning outcomes that had not yet reached the expected standards, particularly in the Pancasila Education subject. Approximately 20% of Grade XI students at SMAN 1 Kamang Magek had not met the minimum achievement criteria. This condition occurred due to students’ lack of interest during the learning process. Therefore, Quizizz-based learning media was implemented as an effort to improve students’ learning outcomes. The purpose of this study was to determine the effect of Quizizz learning media on students’ learning outcomes in Pancasila Education. The research employed a quantitative experimental method with a Pretest-Posttest Control Group Design. The study was conducted at SMAN 1 Kamang Magek, Agam Regency, West Sumatra. The population consisted of all Grade XI students totaling 90 individuals. The sample was determined through a random sampling technique, resulting in two homogeneous classes with a total of 61 students. The data analysis results showed that there was a positive and significant effect between the use of Quizizz learning media and students’ learning outcomes. The obtained values were t_count = 3.290 > t_table = 2.001 and sig. (2-tailed) = 0.002 < 0.05. Thus, the alternative hypothesis (Ha) was accepted. In conclusion, the Quizizz learning media was effective in increasing students’ interest and learning outcomes in Pancasila Education for Grade XI students of SMAN 1 Kamang Magek.